Karakterisasi dan Keragaman Genetik Mutan Padi Inpago Unram 1 Generasi Kedua (M2) Akibat Iradiasi Sinar Gamma: Characterization And Genetic Diversity Of Inpago Unram 1 Rice Mutants Of Second Generation (M2) Due To Gamma Ray Irradiation - Ni Wayan Sri Suliartini; Mita Sapitri; I Wayan Sudika; I Gusti Putu Muliarta Aryana; Anak Agung Ketut Sudharmawan (LPPM Universitas Mataram, 2022)
This study aims to determine the quantitative character of the mutant genotype (M2) and the genetic diversity of the mutant (M2) due to gamma ray irradiation. This experiment was carried out from June to October 2021 in Nyurlembang Village, Narmada District, West Lombok Regency, West Nusa Tenggara, using a Randomized Block Design (RAK) in a partitioned design with a total of 27 treatments consisting of 24 mutant plant genotypes and 3 comparison plants. The results of the observations were analyzed using analysis of variance at a level of 5%, then significantly different treatments were further tested using the Central Significant Difference (BNT) test at a level of 5%. The results showed that gamma ray irradiation caused differences in the characters of each genotype, including the character of plant height, panicle length, number of empty grains, flowering age, and harvest age. The genetic diversity of the M2 generation mutant brown rice (Inpago Unram Satu) due to gamma ray irradiation of 200 Gy shows the character of the number of filled grain, the number of empty grains, and the weight of the filled grain, while other characters have a narrow genetic variation.